Factors Determining the Ability and Willingness to Pay for University Accommodation by Uganda Christian University Students. - Kasande Rachael (Uganda Christian University, 2024)
This dissertation explores the complex realm of the factors determining the demand and willingness to pay for hostel fees among students at Uganda Christian University (UCU). The research focuses on three primary objectives: financial capacity, socio-demographic factors, and perceived values and preferences. Through a quantitative, predictive, cross-sectional survey design, a cross-sectional survey was used to obtain data from multiple sources at one point in time, data was collected from a sample of students residing in key hostels in and around UCU, such as Sabiiti, Nsibambi, Premium, and Sky Courts. The findings reveal that financial capacity (B=2.412, T=-2.861, P=0.005), socio-demographic factors (B=0.488, T=4.333, P=0.000) and perceived value and preferences (B=0.260, T=2.525, P=0.013) all significantly determine the demand and willingness to pay for university accommodation. Financial capacity having a significant negative relationship indicates that the demand and willingness to pay for university accommodation decreases as one's financial capacity decreases. Although many students benefit from adequate financial support from family or other sources, a significant portion still experiences financial insecurity, impacting their ability to afford hostel fees. Socio-demographic factors, particularly overall health and family support, emerged as critical in shaping students' housing decisions, while cultural and social backgrounds were less influential. The regression analysis yielded an Adjusted R square value of 0.200(20%) and an R square value of 0.219(21.9%) indicating that 20% of the variance in demand for university accommodation is explained by financial capacity, socio-demographic factors, and perceived value and preferences. Among the individual factors, socio-demographic factors emerged as the strongest predictor explaining a significant portion of the variance in demand. Additionally, perceived values, such as safety, security, and the convenience of accommodation location, were identified as top priorities too for students significantly influencing student choices, with moderate satisfaction reported regarding the overall quality and value of the available accommodation options. The study concludes that enhancing financial support systems, improving accommodation safety and convenience, and addressing the perceived value of hostel facilities are essential for better aligning UCU’s housing offerings with student needs. These findings contribute to the existing literature by highlighting the unique context of UCU students and providing actionable recommendations for university housing policy. Future research should explore the long-term impacts of financial and housing policy interventions on student well-being and academic success.